Worlds at Our Fingertips: Reading (in) What Remains of Edith Finch. Issue 7 (2nd May 2019) - Bozdog, Mona; Galloway, Dayna
Video games are works of written code that portray worlds and characters in action and facilitate an aesthetic and interpretive experience. Beyond this similarity to literary works, some video games deploy various design strategies that blend gameplay and literary elements to explicitly foreground a hybrid literary/ludic experience. We identify three such strategies: engaging with literary structures, forms, and techniques; deploying text in an aesthetic rather than a functional way; and intertextuality. This article aims to analyze how these design strategies are deployed in What Remains of Edith Finch to support a hybrid readerly/playerly experience. We argue that this type of design is particularly suited for walking simulators (or walking sims) because they support interpretive play through slowness, ambiguity, narrative, and aesthetic aspirations. Understanding walking sims as literary games can shift the emphasis from their lack of "traditional" gameplay complexity and focus instead on the opportunities that they afford for hybrid storytelling and for weaving literature and gameplay in innovative and playful ways.